Imaging the shallow crust with local and regional earthquake tomography. Issue 5 (23rd May 2013) - Biryol, Cemal B.; Leahy, Garrett M.; Zandt, George; Beck, Susan L.
Abstract: [1] While active‐source imaging (seismic reflection, refraction) is typically used to image the shallow crust, these techniques tend to suffer from energy penetration problems in complex tectonic regimes, resulting in poor imaging. Further, active sources (such as air guns or vibroseis) tend to be band limited, resulting in poor signal‐to‐noise ratio at low frequencies (1–10 Hz). Recent studies suggest that earthquake data may be able to solve these imaging problems. However, conventional earthquake tomography typically aims to image the upper mantle and lithosphere, where typical station spacing (tens of km) and array aperture (hundreds of km) have resulted in the maximum resolution. In this study, we take advantage of the small‐scale and 250 m station spacing of the LaBarge Passive Seismic Experiment to determine whether local and regional earthquake tomographies can be used to constrain structure in the top 5 km of the crust. We also study how the inclusion of finite‐frequency effects impacts the final images. Our results indicate that local and regional events provide substantial improvements over teleseismic events alone, with approximately 500 m resolution both vertically and laterally in the upper most 5 km. We also find that inclusion of finite‐frequency data between 1 and 10 Hz plays a key role in maintaining resolution in the shallowest portion of the model. Key Points: Local, regional earthquake tomography are used to reveal upper crustal structure Finite‐frequency approximation helps to obtain more detailed crustal images Images can provide starting models for higher resolution active‐source studies